COMPARATIVE STUDY OF SHEETA AND USHNA FORM OF MANJISTHADI LEPA IN MANAGEMENT OF ANKLE SPRAIN - Hegde Pallavi; P.Hemanth Kumar (International Journal of Applied Ayurved Research, 2016)
The history of an ankle sprain is usually that of an inversion-type twist of the foot followed by pain and swelling. An individual with an ankle sprain can almost always walk on the foot, albeit carefully and with pain. Approximately 85% of such sprains are inversion sprains of the lateral ligaments, 5% are eversion sprains of the deltoid or medial ligament, and 10% are syndesmotic injuries. Posttraumatic osteoarthritis is common in patients with repetitive ankle injuries. In context of Asthi-Bhagna and Vrana-Chikitsa, AcharyaSushruta describes the application of Lepa in condition having Ugra Ruja(severe pain). In classics we do not get direct reference of sprain. Acharya Sushruta in the context of Asthi-Bhagna has mentioned “Patanabhighatadwa” which means Patana(fall), Abhighata(trauma) or both are the main causes for Shotha(swelling), where he has emphasized the use of SheetaParisheka(cold irrigation) and application of SheetaPradeha(cold application), to reduce Vedana and Shotha. The study was carried on 40 patients with 20 in each group, namely group A(Sheeta Manjisthadi Lepa application) and group B (Ushna Manjisthadi Lepa application) for seven days. In both groups marked improvement was noted in all patients. Explanation for use of Sheeta lepa is advised in text, an attempt is made to study Ushna lepa in Ankle sprain. Study revealed that Sheera lepa is beneficial acute condition and Ushna lepa in Chronic Ankle sprain.